Downscaled climate change projections for Wa District in the Savanna zone of Ghana - Tachie-Obeng, E.; Hewitson, B.; Gyasi, E.A.; Abekoe, M.K.; Owusu, G. (Journal of Disaster Research, 2014)
The possibility of future climate change in Ghana has received much attention due to repeated droughts and floods over the last decades. The savanna zone which is described as the food basket of Ghana is highly susceptible to climate change impact. Scenarios from 20- year time slices of the near future - 2046-2065 - and the far future - 2081-2100 - climate change meant to help guide policy remain a challenge. Empirical downscaling performed at the local-scale of Wa District in the savanna zone of Ghana under the IPCC A2 SRES emissions scenario showed evidence of probable climate change with mean annual temperatures expected to increase over an estimated range of 1.5°C to 2.3°C in the near future, with number of cool nights becoming less frequent, especially during the Harmattan1 period. The dry season is expected to be warmer than the wet season, with high inter-annual variations projected in both maximum (Tmax) and minimum (Tmin) temperatures. Given an average of 1 day of Tmax > 40°C per month in the control period of 1961-2000, the number of hot days is expected to increase to 12 by 2046-2065. An increase in total rainfall is projected with possible shifts in distribution toward the end of the year, with a slight increase in rainfall during the dry season and an increase of rainfall at the onset and toward the end of the wet season. However, a decrease in June rainfall is projected in the wet season. The objective of this paper is to improve the understanding of future climate as a guide to local level medium-term development plans of effective adaptation options for Wa district in the savanna zone of Ghana.
Keywords: Climate-projected climate scenario; Ghana; Rainfall; Temperature